Stem cell and tissue engineering - Li, Song, 1965-; L'Heureux, Nicolas, 1966-; Elisseeff, Jennifer H. (World Scientific, 2011)
Tissue engineering integrates knowledge and tools from biological sciences and engineering for tissue regeneration. A challenge for tissue engineering is to identify appropriate cell sources. The recent advancement of stem cell biology provides enormous opportunities to engineer stem cells for tissue engineering. The impact of stem cell technology on tissue engineering will be revolutionary. This book covers state-of-the-art knowledge on the potential of stem cells for the regeneration of a wide range of tissues and organs and the technologies for studying and engineering stem cells. It serves.